Effects of Replacing Inorganic Sources of Copper, Manganese, and Zinc with Different Organic Forms on Mineral Status, Immune Biomarkers, and Lameness of Lactating Cows - Manqian Cha; Xingjun Ma; Yunlong Liu; Shengyang Xu; Qiyu Diao; Yan Tu (Animals)
(Objectives) The objectives of this study were to evaluate the effect of half-replacement of the supplementary sulfate sources of Cu, Mn, and Zn with methionine-hydroxy-analog-chelated (MHAC) mineral or amino-acid-complexed (AAC) mineral forms in diets on the mineral status, blood immune biomarkers, and lameness of lactating cows. (Methods) Sixty multiparous Holstein cows (158 ± 26 days in milk; body weight: 665 ± 52 kg; milk yield: 32 ± 7 kg/day) were randomly assigned into one of three dietary treatments (n = 20 per group): (1) MHAC: 50% replacement of sulfate minerals with MHAC forms. (2) AAC: 50% replacement of sulfate minerals with AAC forms. (3) S: 100% sulfate minerals (control). Their Cu, Mn, and Zn concentrations, blood immune biomarkers, and lameness were measured monthly. Repeated-measure mixed models were used to evaluate the effects on trace mineral status over time. As the responses with the MHAC and AAC forms were similar, the treatments were also analyzed as organic trace minerals (OTMs, combining the MHAC and AAC groups, n = 40) versus inorganic trace minerals (ITMs, the S group, n = 20). (Results) Cows supplemented with OTMs had higher concentrations of Cu and Mn in their serum (p ≤ 0.05), a higher hoof hardness (p ≤ 0.05), and a lower incidence of lameness compared to those with ITMs on d 90. There were no statistical differences (p > 0.10) in the concentrations of IgA, IgG, or ceruloplasmin, but there were significant differences (p = 0.03) in the concentrations of IgM in the serum as fixed effects of the diet treatments during the whole trial. On d 30 and 90, the serum IgA concentrations of the cows supplemented with OTMs tended to be higher (0.05 < p ≤ 0.10) than those in the cows supplemented with ITMs. (Conclusions) The half-replacement strategy showed that the MHAC and AAC sources of Cu, Mn, and Zn additives had similar effects on the production performance, blood immune biomarkers, and lameness of the lactating cows. The long-term replacement strategy with OTMs led to the enhancement of the trace mineral concentrations in their body fluids, blood immune biomarkers, and hoof health.